Development of core-shell scaffold with GelMA for cell encapsulation - Zhu, Jayden Houyu (2018)
There are around 20 million Type 1 diabetic patients worldwide and the only curative treatment involves islet transplantation. However, the shortage of donors and lifelong immunosuppression side effect drives the need for new regeneration treatment. Among all the approaches, cell encapsulation appeared to be the promising one. The main challenge in cell encapsulation is on how to ensure the viability and proliferation of the cells, while keeping the encapsulating material harmless to the body. Gelatin methacrylate (GelMA) emerged as the potential encapsulating material due to its excellent biocompatibility, tailorable mechanical properties and low immunoresponse. However, limited research has been done to investigate the feasibility of tuning the degree of substitution of GelMA to encapsulate the cells. In this study, we will be examining the Core-Shell scaffold made with GelMA. Type A gelatin will be used to synthesize the GelMA required for the study, and various degree of substitution of the GelMA with different concentration will be involved. The stiffness and storage modulus of these GelMA samples were studied using rheology test, and the result showed that stiffness and storage modulus are subjected to the degree of substitution(DS) and concentration of the GelMA. Moreover, temperature has a significant impact on the stiffness. The pores structure was observed using SEM, and the data showed that smaller pores size and greater pore density were associated with higher degree of substitution and concentration. 25DS GelMA with 10% w/v as the core material and 75DS GelMA with 30% w/v as the shell material were selected for the Core-Shell scaffold. Live/Dead test was performed to prove the viability of cells in the Core-Shell scaffold made using GelMA. In summary, encapsulation of cells using the Core-Shell scaffold made with GelMA is feasible and able to maintain cell viability.